The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4141/cjss10029
|View full text |Cite
|
Sign up to set email alerts
|

Predicting soil organic carbon and total nitrogen using mid- and near-infrared spectra for Brookston clay loam soil in Southwestern Ontario, Canada

Abstract: Xie, H. T., Yang, X. M., Drury, C. F., Yang, J. Y. and Zhang, X. D. 2011. Predicting soil organic carbon and total nitrogen using mid- and near-infrared spectra for Brookston clay loam soil in Southwestern Ontario, Canada. Can. J. Soil Sci. 91: 53–63. Mid-infrared (MIR) and near-infrared (NIR) spectroscopy of soils have been tested to estimate soil organic carbon (SOC) and total N (TN) concentrations at local, regional and national scales. However, these methods have rarely been used to assess SOC and TN conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 48 publications
4
50
2
1
Order By: Relevance
“…As can be seen in Table 3, 2 R regression value was found as 0,793 and residual prediction 2 deviation value as 2.0802. R and the RPD values calculated in this study for the prediction of total nitrogen were lower than that of previous studies (Xie et al, 2011;Wenjun et al, 2014). Many researchers have reportedsuccessful application of thevis-NIR spectroscopy for the prediction of various soil characteristics.…”
Section: Resultscontrasting
confidence: 71%
“…As can be seen in Table 3, 2 R regression value was found as 0,793 and residual prediction 2 deviation value as 2.0802. R and the RPD values calculated in this study for the prediction of total nitrogen were lower than that of previous studies (Xie et al, 2011;Wenjun et al, 2014). Many researchers have reportedsuccessful application of thevis-NIR spectroscopy for the prediction of various soil characteristics.…”
Section: Resultscontrasting
confidence: 71%
“…The results of the Cubist models for predicting SOC and TN under field conditions were satisfactory and compared favourably with results from studies using dried and homogenized soil samples in the laboratory (Chang et al 2001;Martin et al 2002;Xie et al 2011). Our results compare favourably with a study in Australia that used a portable spectrometer to measure SOC contents in the field, as we were able to obtain a RPD value of 2.2 compared with 1.92 in the study in Australia (Gomez et al 2008b).…”
Section: Modelmentioning
confidence: 65%
“…While work conducted in the Canadian provinces of Manitoba and Ontario has successfully shown that reflectance spectroscopy can be used to predict SOC and TN (Martin et al 2002;Xie et al 2011), there is a lack of information on the use of reflectance spectroscopy on Canadian soils and more specifically, Alberta soils. The processing of soil spectral data has focused on using partial least squares regressions (e.g., Gomez et al 2008aGomez et al , 2008bXie et al 2011;Kinoshita et al 2012) and using signal processing techniques such as Savitzky-Golay smoothing, derivatives, and multiplicative scatter correction (e.g., He et al 2007;Minasny et al 2009;Doetterl et al 2013;Nawar et al 2016). Recently, two data processing techniques have been applied to spectral data and have improved the accuracy of model predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Luce et al, 2012;Xie et al, 2011;Zornoza et al, 2008). The VNIRS was also used for prediction of MBN (Coûteaux et al, 2003;Ludwig et al, 2002;Reeves and McCarty, 2001;Terhoeven-Urselmans et al, 2008).…”
Section: Introductionmentioning
confidence: 99%